Production Characteristics of Ergonomics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, the image that appears in the mind of the addressee when perceiving this or that name is more or less abstract from the activity of the named enterprise. It is said that the nominator chooses an associative-figurative name based on the "width of semantics" and the figurative objective and subjective associations perceived by the addressee associated with the word or words used in the name.